Improving Learning Motivation and Mathematical Problem-solving abilities via vernier Caliper Virtual Labs - Nazilah, Novia Rohmatun; Agustia, Fira; Maharani, Anggita; Hartono , Wahyu (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
The low learning motivation and mathematical problem-solving abilities of vocational high school students, regarding mechanical measuring instruments, such as vernier calipers, present a significant challenge in the learning process. Anteractive simulation-based Virtual Lab is expected to be an innovative solution to address these issues. This study aims to examine the effect of using a Virtual Lab on students' learning motivation and mathematical problem-solving abilities. The method used was quantitative with a one-group pretest-posttest design involving 42 Mechanical Engineering vocational high school students. Data were collected through observation sheets, a learning motivation questionnaire, and a mathematical problem-solving test. The results showed that students' learning motivation was in the good category based on observation and questionnaire data, which had high validity and reliability (Cronbach's Alpha = 0.878). Furthermore, students' mathematical problem-solving abilities increased significantly, with the average score rising from 68.95 in the pretest to 79.74 in the posttest. The Wilcoxon Signed Ranks Test confirmed a significant improvement (p < 0.001). However, the results of this study did not show an effect of motivation on problem-solving ability, because it did not comply with the one-group pretest-posttest design. Thus, it can be concluded that the Virtual Lab is effective in improving learning motivation and mathematical problem-solving skills separately in vocational high school students.